2011
DOI: 10.3858/emm.2011.43.6.034
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoids in radioregulation: double edged sword

Abstract: Radiotherapy, frequently used for treatment of solid tumors, carries two main obstacles including acquired radioresistance in cancer cells during radiotherapy and normal tissue injury. Phenylpropanoids, which are naturally occurring phytochemicals found in plants, have been identified as potential radiotherapeutic agents due to their anti-cancer activity and relatively safe levels of cytotoxicity. Various studies have proposed that these compounds could not only sensitize cancer cells to radiation resulting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 94 publications
2
21
0
Order By: Relevance
“…However, the exact mechanism for their action so far has not been fully identified. It has been continuously reported that most of herbals and their derivative compounds were found to have both radioprotecting and radiosensitizing properties (Goel & Aggarwal, 2010;Kim et al, 2011;. The results of this and the former study indeed indicate that D. scandens extract acts as a radioprotector or as a radiosensitizer, depending on the cellular context.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, the exact mechanism for their action so far has not been fully identified. It has been continuously reported that most of herbals and their derivative compounds were found to have both radioprotecting and radiosensitizing properties (Goel & Aggarwal, 2010;Kim et al, 2011;. The results of this and the former study indeed indicate that D. scandens extract acts as a radioprotector or as a radiosensitizer, depending on the cellular context.…”
Section: Discussionsupporting
confidence: 65%
“…Radiosensitizers escalate radiation damage in tumor cells via various mechanisms such as increase in initial DNA damage, interfere or inhibit DNA damage repair, cell cycle control, cell survival or cell death pathways (Girdhani et al, 2005;Javvadi et al, 2008;Shin et al, 2008;Katz et al, 2009;Verheij et al, 2010). Radioprotectors are compounds that diminish damaging effects of radiation to normal cells mostly via their ability to scavenge free radicals generated by ionizing radiation (Maurya et al,1 has been of interest of investigators for decades, only very few compounds have been approved for clinical application because of non-specificity and unacceptable toxicity (Katz et al, 2009;Habr-Gama et al, 2010;Kim et al, 2011). It has been proposed that the use of naturally occurring compounds derived from herbal medicinal plants as radiomodulators is less toxic within certain doses .…”
Section: Introductionmentioning
confidence: 99%
“…Genes related to phynelpropanoid metabolism pathways have been reported to be up-regulated under pathogenic or wounding events (Turner et al, 2012). Phenylpropanoids have been also investigated as a potential cancer treatment and chemopreventive agents (Bruyère et al, 2011;Itoigawa et al, 2004;Kim et al, 2011). Eugenol has antitumor properties associated with apoptosis in different cancer cells (Liang et al, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…As radiation effects do not discriminate between normal and malignant cells and tissue, patients may experience symptoms during the course of therapy for a few weeks after therapy or months or years later (Karbownik & Reiter, 2000). Several modalities and clinical approaches have been made to reduce these early and late complications of the radiotherapies and one among them is the use of an effective and nontoxic radio-protector (Kim, Seong, & Youn, 2006). Radioprotectors are compounds that are designed to reduce the damage in normal tissue caused by radiation.…”
Section: Introductionmentioning
confidence: 99%